Composting fruit and vegetable waste using black soldier fly larvae - Irfana Kabir Ahmad,; Zawawi Samba Mohamed,; Nur Fardilla Amrul,; Chong, Wai Quan; Nurul Ain Abdul Jalil,; Noor Ezlin Ahmad Basri,; Mohd Reza Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
In recent years, the amount of solid waste generated has been increasing, and larger land space is needed for the disposal of the generated waste. One of the ways to deal with the limited landfill space is by composting organic waste using black soldier fly larvae. This study aims to determine the percentage of BSFL growth and to assess the effectiveness of using BSFL in composting fruits, boiled vegetables, and raw vegetables. The waste used in this study was collected from the college cafeteria and sorted into three waste categories, and 100g of each waste category was placed in different containers. Two different sets of experiments were carried out using an initial weight of 2g and 4g of BSFL. Within 17-days experiment, the weight of BSFL and composted waste were measured every three or four days, also an additional 100g of new waste was added to the containers until the amount of waste reached a total of 500g. The BSFL fed with the fruit waste has the highest growth percentage of 1700% relative to their initial weight of 2g. The BSFL with a higher initial density of 4g showed a lower percentage growth of 1200%. Fruit waste showed the highest percentage of weight reduction of 57%. This study has proven that fruit waste is a more suitable medium for larval growth compared to vegetable waste. The use of BSFL in organic waste composting is an effective method for reducing the amount of wastes disposed of in landfills.